The girls who went away the hidden history of women who surrendered children for adoption in the decades before Roe v. Wade - Fessler, Ann (Penguin Press, 2006)
This book brings to light the lives of 1.5 million single American women in the years following World War II who, under enormous social and family pressure, were coerced to give up their newborn children. It tells not of wild and carefree sexual liberation, but rather of a devastating double standard that has had punishing long-term effects on these women and on the children they gave up. Single pregnant women were shunned by family and friends, evicted from schools, sent away to maternity homes to have their children alone, and often treated with cold contempt by doctors, nurses, and clergy. The majority of the women interviewed by Fessler, herself an adoptee, have never spoken of their experiences, and most have been haunted by grief and shame their entire adult lives.--From publisher description.